Analysis of seed vigor and germination of Toona ciliata M. Roem. var. australis - Lucchese,Júlio Rieger (2018)
Abstract: Seed analysis tests should be performed under standard conditions for each species, so that the results can be reproducible anywhere. Seeds of the forest species Toona ciliata var. australis have been commercialized in Brazil despite no standard conditions for their analysis have been published. The objective was to determine basic information about temperature and photoperiod for the germination test and the imbibition time and volume of water for electrical conductivity. In the germination test the seeds were incubated at 15, 20, 25 and 30 °C with 0, 12 and 16 h of light. The electrical conductivity was evaluated up to 108 h after immersion of the seeds in 50 and 100 mL of deionized water. The conditions of 25 °C and 16 h of light provided higher amount of normal seedlings. At 15 °C all seeds remained hard regardless the photoperiod used, however, it became absent when light was added at higher temperatures. The electrical conductivity test should be performed with a volume of 50 mL and evaluated after 24 h of imbibition. It also showed a stronger correlation between normal seedlings, being a promising vigor evaluation test for this species.